Student academic stress during the COVID-19 pandemic: a systematic literature review - Hamidulloh Ibda; Tri Suraning Wulandari; Aufa Abdillah; Asih Puji Hastuti; Mahsun Mahsun (International Journal of Public Health Science (IJPHS), 2023)
This article presents systematic literature review related to student academic stress during the COVID-19 pandemic in the latest literature. Although there have been similar studies, there are still few that present the newest literature review related to student academic stress during the pandemic. This article uses the systematic review literature method to identify, evaluate, and interpret existing research results with the help of Publish or Perish version 7, VOSviewer, and NVIVO 12 plus applications. The release of articles in scopus indexed journals is limited to three years, namely 2020-2022. From the search results in the Publish or Perish version 7 application, there are 248 articles indexed by Scopus, then selected papers according to compatible themes into 50 pieces. The findings of the topics are stress, students, academic-related stress, academic performance, posttraumatic stress disorder, health psychology, academic achievement, emotional intelligence, depression, COVID-19, online exam, academic success, academic engagement, insomnia, and coping. These 50 articles were analyzed according to the topics set through the NVIVO 12 plus application and described the results according to research questions. This article contributes to subsequent research and studies the theme of student academic stress during the pandemic.